Development of virtual reality-based educational game to improve student’s computational thinking skills - Prasetyo, Wanes; Pramudita, Dias Aziz (AIP conference proceedings, 2023)
Referring to the 2018 PISA test results data, the thinking ability of students in Indonesia is in the bottom 10. This encourages the government to make improvements to the curriculum that can prepare children to compete on international standards with a focus on the needs of the 21st-century industry. Abilities Computational Thinking needs to be developed to expand thinking skills. Learning media is needed that supports students in practicing their skills in Computational Thinking. The use of game media or other technologies such as Virtual Reality has the characteristics that it can be developed and implemented as a new alternative in the delivery of the learning process. The purpose of this research is to develop an educational game Computational Thinking based on VR Computhink to improve students’ computational thinking skills. The research uses the R&D method combined with the ADDIE product development model with stages covering Analysis, Design, Development, Implementation, and Evaluation. The subject of the media test on class VI students using the SUS method and testing of material experts and media experts by collecting data using a questionnaire. It was found that the VR-based educational game Computhink obtained an assessment result from students with a score of 80.56 while material experts obtained a score of 95% in the aspect of learning media. Media experts obtained an average score of 87.50% for the learning design aspect and 88.00% for the learning communication aspect. So that it is stated that the Computhink VR-based educational game is feasible to be implemented for students.